2022
DOI: 10.1016/s2665-9913(21)00327-1
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of two doses of the CoronaVac SARS-CoV-2 vaccine in SARS-CoV-2 seropositive and seronegative patients with autoimmune rheumatic diseases in Brazil: a subgroup analysis of a phase 4 prospective study

Abstract: Background We aimed to examine the immunogenicity pattern induced by the inactivated SARS-CoV-2 vaccine CoronaVac (Sinovac Life Sciences, Beijing, China) in SARS-CoV-2 seropositive patients with autoimmune rheumatic diseases compared with seropositive controls, seronegative patients with autoimmune rheumatic diseases, and seronegative controls. Methods CoronavRheum is an ongoing, prospective, controlled, phase 4 study, in which patients aged 18 years or older with autoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
48
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 28 publications
0
48
0
Order By: Relevance
“…10 A more robust response was observed in individuals with ARD pre-exposed to COVID-19, with a high plateau of response after a single Coro-naVac dose. 13 Neutralising antibodies' (NAb) response dynamics in patients who have recovered from COVID-19 may vary greatly. 14 We further demonstrated a substantial decline of anti-SARS-CoV-2 antibodies in patients with ARD 6 months after a two-dose schedule of CoronaVac.…”
Section: Introductionmentioning
confidence: 99%
“…10 A more robust response was observed in individuals with ARD pre-exposed to COVID-19, with a high plateau of response after a single Coro-naVac dose. 13 Neutralising antibodies' (NAb) response dynamics in patients who have recovered from COVID-19 may vary greatly. 14 We further demonstrated a substantial decline of anti-SARS-CoV-2 antibodies in patients with ARD 6 months after a two-dose schedule of CoronaVac.…”
Section: Introductionmentioning
confidence: 99%
“…This study provides evidence that, in patients with autoimmune rheumatic diseases who have been exposed to natural SARS-CoV-2 infection, a single dose of CoronaVac might be sufficient to produce robust antibody responses, by contrast with unexposed individuals who need at least two doses. 3 Several previous studies of other COVID-19 vaccines showed similar results in the general population or in patients with autoimmune diseases. A single dose of mRNA vaccine or adenovirus-vectored vaccine in patients who had recovered from COVID-19 has been found to elicit similar humoral immunity as elicited by two doses of vaccine in unexposed patients, which is possibly related to the enhanced recall response of pre-existing memory B cells compared with the primary response.…”
mentioning
confidence: 55%
“…In The Lancet Rheumatology, Nadia E Aikawa and colleagues report a subgroup analysis of the CoronavRheum study, 3 comparing CoronaVac immunogenicity in patients with autoimmune rheumatic disease who were SARS-CoV-2 seropositive or seronegative with controls who were seropositive or seronegative. 942 participants were included in the subgroup analysis, of whom 157 were seropositive patients, 157 were seropositive controls, 471 were seronegative patients with autoimmune rheumatic diseases and 157 were seronegative controls (median age was 48 years [IQR 38–56] and 594 [63%] were female and 348 [37%] were male).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, vaccine responses largely vary between individuals. This is the case of immunocompromised individuals who generally exhibit lower immunogenicity to SARS-CoV vaccines, likely due to the disease-related immune dysfunction and the use immunosuppressive, glucocorticoid, and/or biological therapies ( 2 5 ). Prolonged SARS-CoV-2 shedding, decreased SARS-CoV-2 clearance, and enhanced viral genomic evolution have been reported in immunocompromised patients, which underscores the relevance of improving vaccine responses in this population to ultimately prevent the emergence of new variants ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%